Peran Tokoh Agama dalam Penyuluhan Hukum Perkawinan Islam - Sehoni, Sehoni; Fernando, Akel (Journal of Legal Sustainability, 2025)
Religious leaders play a strategic role in educating the public about Islamic marriage law, particularly in the dissemination of sharia values and relevant legal regulations. This study aims to examine the role of religious leaders in the dissemination of Islamic marriage law, focusing on their educational, preventive, and mediative functions. Using a qualitative approach and field research, the study found that religious leaders are not only conveyors of religious teachings but also act as counselors and mediators in resolving household issues. They help bridge the community's understanding of both positive law and Islamic norms related to marriage, including matters such as dowry (mahar), marriage guardians (wali nikah), polygamy, and divorce. The findings show that the effectiveness of legal counseling largely depends on the credibility of the religious leaders, the approach and methods they employ, as well as institutional support from both the government and the community. Therefore, strengthening the capacity of religious leaders in legal counseling is an urgent need in order to foster harmonious families that align with the principles of Islamic law.